2011
DOI: 10.5483/bmbrep.2011.44.6.405
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of human GM3 synthase (hST3Gal V) gene by valproic acid in ARPE-19 human retinal pigment epithelial cells

Abstract: The present study demonstrated that valproic acid (VPA) transcriptionally regulates human GM3 synthase (hST3Gal V), which catalyzes ganglioside GM3 biosynthesis in ARPE-19 human retinal pigment epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Cell viability assay was performed as described previously [7,8,9,10,11]. The amount of formazan produced was quantified by measuring the absorbance at 490 nm with an ELISA plate reader (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability assay was performed as described previously [7,8,9,10,11]. The amount of formazan produced was quantified by measuring the absorbance at 490 nm with an ELISA plate reader (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently we studied the transcriptional regulation mechanism of human sialyltransferase genes that are specifically expressed at high levels in cell lines treated with natural compounds [7,8,9,10,11]. In the current study, we investigated the effect of physcion isolated from the Polygonum multiflorum roots on the human sialyltransferase gene expression in SK-N-BE(2)-C human neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…1-4). Valproic acid is a known up-regulator of GM3 synthase gene (16), and it is also known as an inhibitor of histone deacetylase (14,15). Therefore, it is possible that valproic acid may control the expression of other genes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to GM3, valproic acid, which is known as an anticonvulsant and mood-stabilizing drug and a histone deacetylase inhibitor (13)(14)(15), has been shown to up-regulate ST3GAL5 gene expression (16). In a recent clinical trial, the potential application of valproic acid in treating cancers, especially high grade gliomas, was examined, and it was observed that valproic acid had some therapeutic effect on glioma (17).…”
Section: Glycosphingolipid Gm3mentioning
confidence: 99%
See 1 more Smart Citation